Exploring Gender Roles in Mobile Legends: A Study of Women's Involvement in Online Games - Arif Rizki ZURRIANSYAH; Susiyanto SUSIYANTO; Lesti HERIYANTI (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2025)
This study aims to explore women's involvement in the game Mobile Legends: Bang Bang (MLBB) from the perspective of their subjective experiences. Using a qualitative phenomenological approach, this study involved eight female informants who actively play MLBB and have social experiences within the gaming community. The results show that women play four main roles: as active and strategic players, recipients of gender pressure, agents of resistance and adaptation, and representative symbols within the community. Despite facing various forms of discrimination and symbolic violence, the informants are able to navigate these challenges through contextual strategies of resistance and adaptation. These findings support theories of social construction and gender performativity and emphasize the importance of digital space as an arena for negotiating gender identity.